2016
DOI: 10.18632/oncotarget.9737
|View full text |Cite
|
Sign up to set email alerts
|

In-depth mapping of the mouse brain N-glycoproteome reveals widespread N-glycosylation of diverse brain proteins

Abstract: N-glycosylation is one of the most prominent and abundant posttranslational modifications of proteins. It is estimated that over 50% of mammalian proteins undergo glycosylation. However, the analysis of N-glycoproteins has been limited by the available analytical technology. In this study, we comprehensively mapped the N-glycosylation sites in the mouse brain proteome by combining complementary methods, which included seven protease treatments, four enrichment techniques and two fractionation strategies. Altog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 41 publications
0
39
0
Order By: Relevance
“…Overlap in glycosites from this study and two deglycoproteomic experiments were performed from Zielinska et al and Fang et al studies. 66,67 Gene ontology enrichment analysis was performed using DAVID 68 with a mouse brain proteome as the background. 69 The protein-glycan network, glycan co-occurrence networks, and glycosylation profiles for subcellular groups were created in R 3.2.2 using the igraph library, 70 and the arcplot were created with arcdiagram library (Sanchez, G. arcdiagram: Plot pretty arc diagrams.…”
Section: Discussionmentioning
confidence: 99%
“…Overlap in glycosites from this study and two deglycoproteomic experiments were performed from Zielinska et al and Fang et al studies. 66,67 Gene ontology enrichment analysis was performed using DAVID 68 with a mouse brain proteome as the background. 69 The protein-glycan network, glycan co-occurrence networks, and glycosylation profiles for subcellular groups were created in R 3.2.2 using the igraph library, 70 and the arcplot were created with arcdiagram library (Sanchez, G. arcdiagram: Plot pretty arc diagrams.…”
Section: Discussionmentioning
confidence: 99%
“…While glycans were shown to be specifically enriched in synapses 148, 149 , the intra-CNS expression of GP2 and GM-CSF in the developing or mature brain is still lacking. However, two recent MRI studies performed in CD patients demonstrated marked structural brain alterations 150, 151 that correlated with cognitive dysfunction 150 .…”
Section: The Cns Is a Major Source Of Superautoantigensmentioning
confidence: 99%
“…Given that both N - and O -linked CDGs present with abnormal development of other brain structures, and animal models with altered sialylation show distinct neurodevelopment defects, it is possible that the altered glycosylation we observe in JBTS10 patients may contribute to the formation of MTS. Recent work by Feng and colleagues to identify the N -glycoproteome in the mouse brain revealed that several key proteins for brain development are N -glycosylated [52]. …”
Section: Discussionmentioning
confidence: 99%